Papillon-Lefevre syndrome: A case report - Kalwa Pavankumar (Elsevier, 2010)
Papillon-Lefevre syndrome (PLS) is a rare autosomal recessive disorder of keratinization, characterized by palmoplantar hyperkeratosis, periodontal involvement and precocious loss of dentition. The purpose of this report was to describe the case of an 18-year-old girl who presented to the out patient department of Navodaya Dental College and Hospital, Raichur, Karnataka, India, with the chief complaint of multiple loss of teeth. Her gingiva appeared erythematous, edematous and bled readily on probing, and the teeth were mobile. Hyperkeratosis of palms and soles were found. These findings are consistent with Papillon-Lefèvre syndrome. The clinical presentation, differential diagnosis, complications and management of this syndrome are discussed. Keywords: Papillon-Lefevre syndrome, Palmoplantar hyperkeratosis, Premature tooth loss, Periodontitis